Movement parameters of persons with disabilities on evacuation by lifts - Szénay, Martin; Lopušniak, Martin (Collective Dynamics, 2020)
In 2010 it was defined five challenges for the solution of evacuation of persons in buildings to 2020. One of the challenges is to implement helpfull technologies during evacuations from buildings – lifts. Needed steps for fulfilling this challenge are also quantification of missing data which are dealing with evacuation of persons with disabilities. From 2002 all public buildings in Slovak Republic have to be also accessible to persons with disabilities, but it is also a global problem. In present exists just small number of informations of movement parameters of persons with disabilities during evacuation by lift. There for, this work was focused on collecting these informations. The data collection was realized by using an in-situ experiment. The aim of the work was to quantify the phase stages of evacuation by elevators for persons with disabilities (speed, time, movement and capacity parameters). Person’s movements were monitored during the measurements, arrival to lift, cabin entry and exit from the cabin, including leaving the bounded area. Arrival to lift included movement in the bounded area in front of the lift, until the moment of pushing the button was pressed to call the lift. The time of cabin entering includes the time from the beginning of opening the lift doors to the beginning of closing of the lift doors. The exit from the cabin includes the time from opening the lift doors, passing through the lift doors to leaving the bounded area. In total, ten participating persons in the experiments imitated wheelchair movement and movement with leg fracture. Measurements were made on two lifts, where person evacuating himself or with the help of another person. Everyone performed each measurement three times. A total of 720 measurements were performed in the work. According to the results of the experiment it can be stated that cabin entry is longer for a person on the wheelchair than for a person with a leg fracture, but the difference is even bigger during exit from the cabin, including leaving the bounded area. During the experiment, various movement techniques have been observed that may affect their overall the time of cabin entry and exit from the cabin. Obtained results can extend existing evacuation model to the possibility of using the lift. The obtained results quantify the individual phase stages of entering to the lift and exiting of the lift for persons with limited movement.